Strategies for Managing Chronic Diseases Based on the Perspective of Bioethics and Human Rights Within the Framework of Health Law of The Republic of Indonesia Number 17 on year 2023 - Ni Putu Purnianti; Ida Bagus Gede Fajar Manuaba (Dinasti Research, 2025)
The increasing prevalence of chronic diseases in Indonesia requires serious attention to management strategies. This study aims to analyze chronic disease management strategies within the framework Health Law of the Republic of Indonesia Number 17 on year 2023 incorporating bioethical perspectives and human rights (HR). The approach ensures that health policies address not only technical and administrative aspects but also respect ethical values and justice. Using a qualitative method with a policy analysis approach, the research involves literature review, regulation analysis, and in-depth interviews with health and legal experts. The findings highlight bioethical principles, such as patient autonomy, equitable access to healthcare, and non-maleficence, which are key in supporting fair and inclusive policies. Furthermore, the right to health as part of HR emphasizes the importance of providing equitable services, particularly for vulnerable groups like chronic disease patients. The study concludes that the implementation of Health Law of the Republic of Indonesia Number 17 on year 2023 should consistently adhere to bioethics and HR principles to create a holistic, just healthcare system.